Drivers of 'voluntary' recruitment and challenges for families with adolescents engaged with armed groups: Qualitative insights from Central African Republic and Democratic Republic of the Congo. - Alexandra H Blackwell; Yvonne Agengo; Daniel Ozoukou; Julia Ulrike Wendt; Alice Nigane; Paradis Goana; Bertin Kanani; Kathryn Falb (Public Library of Science (PLoS), 2023)
Globally, armed conflicts have increased threefold since 2010. The number of children voluntarily engaging with armed groups is also rising, despite increasing efforts to prevent this grave human rights violation. However, traditional approaches focusing on the prevention, release, and reintegration of children through forced recruitment do not adequately address the complex and interlinking push and pull factors of voluntary recruitment. This qualitative study sought to deepen understanding of the drivers and consequences of voluntary recruitment from the perspectives of adolescents and their caregivers, as well as to explore how to better support families living in conflict settings. In-depth interviews were conducted with 74 adolescents (44 boys and 30 girls) ages 14 to 20 years and 39 caregivers (18 men and 21 women) ages 32 to 66 years in two distinct conflict settings: North Kivu, Democratic Republic of Congo and Ouham-Pendé, Central African Republic. Interviews with adolescents utilized a visual narrative technique. The findings examine the unique perspectives of adolescents engaged with armed groups and their caregivers to understand how conflict experiences, economic insecurity, and social insecurity influence adolescent's engagement with armed groups and reintegration with their families. The study found that families living in conflict settings are subject to traumatic experiences and economic hardship that erode protective family relationships, leaving adolescent boys and girls particularly vulnerable to the systemic and overlapping factors that influence them to engage with and return to armed groups. The findings illustrate how these factors can disrupt protective social structures, and inversely how familial support can act as a potential protective factor against recruitment and break the cycle of reengagement. By better understanding the experiences of adolescents enduring recruitment and how to support caregivers of those adolescents, more comprehensive programming models can be developed to adequately prevent voluntary recruitment and promote successful reintegration, enabling children to reach their full potential.